Implementasi Tanda Tangan Digital Menggunakan Algoritme RSA dan SHA-512 Berbasis Web - Agnes Aryasanti; Mardi Hardjianto; Goenawan Brotosaputro; Ririt Roeswidiah (Jurnal Ticom: Technology of Information and Communication, 2022)
A document is a written or printed letter used as evidence. Along with the development of technology, currently documents are not only published in physical or printed form, but also in digital form. Digital documents have the same function as physical documents, but have a weakness that is very vulnerable to the possibility of modification, being transferred by anyone and challenging to prove the document authenticity. One way to prevent this is to make a special mark to ensure that the document is genuine. This particular signature is a digital signature. This study uses the hash function SHA-512 to find the hash value, while the public key encryption uses the RSA algorithm. The test results show that a digital signature system using the RSA and SHA-512 algorithms can secure essential documents from changes by irresponsible people. The process of giving digital signatures does not take long, which is less than one second.